1999
DOI: 10.1074/jbc.274.32.22610
|View full text |Cite
|
Sign up to set email alerts
|

Plant Importin α Binds Nuclear Localization Sequences with High Affinity and Can Mediate Nuclear Import Independent of Importin β

Abstract: Nuclear import of conventional nuclear localization sequence (NLS)-containing proteins initially involves recognition by the importin (IMP)␣The entry of karyophilic proteins into the nucleus through the nuclear pore complex (NPC) 1 is effected by specific targeting signals called nuclear localization sequences (NLSs) (1, 2), and is a receptor-mediated (3, 4), energy-dependent (5, 6) process. The key factors involved are members of the NLS-recognizing importin/karyopherin family (7-11), the monomeric GTPase R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
78
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 64 publications
(114 reference statements)
7
78
1
Order By: Relevance
“…All classes of NLS are held to be recognized specifically by the 'NLS-receptor', the α/β-importin heterodimer, during the first step of nuclear transport, as has been shown directly for the importins from several species. [103][104][105][106][107][108] Certain apparently conventional NLS have been demonstrated to be recognized specifically not by the α/β-importin heterodimer, but by importin β (importin β1) alone, such as the T cell protein tyrosine phosphatase, 109 the HIV-1 Rev protein, 110 the yeast transcriptional activator GAL4 111 and parathyroid hormone related protein (PTHrP). 112 All of these proteins appear to be able to be transported to the nucleus in the absence of importin α, which has been shown directly for PTHrP.…”
Section: Targeting Proteins To the Nucleusmentioning
confidence: 99%
“…All classes of NLS are held to be recognized specifically by the 'NLS-receptor', the α/β-importin heterodimer, during the first step of nuclear transport, as has been shown directly for the importins from several species. [103][104][105][106][107][108] Certain apparently conventional NLS have been demonstrated to be recognized specifically not by the α/β-importin heterodimer, but by importin β (importin β1) alone, such as the T cell protein tyrosine phosphatase, 109 the HIV-1 Rev protein, 110 the yeast transcriptional activator GAL4 111 and parathyroid hormone related protein (PTHrP). 112 All of these proteins appear to be able to be transported to the nucleus in the absence of importin α, which has been shown directly for PTHrP.…”
Section: Targeting Proteins To the Nucleusmentioning
confidence: 99%
“…Furthermore, plants possess homologs of many of the proteins known to be involved in nucleocytoplasmic transport in other organisms. These include homologs of importin α (Ballas and Citovsky, 1997;Hubner et al, 1999;Jiang et al, 1998a;Jiang et al, 2001;Smith et al, 1997a;Smith et al, 1997b), importin β (Jiang et al, 1998a), the exportin Crm1/Xpo1 (Haasen et al, 1999), Ran1 (Haizel et al, 1997), RanGAP (Rose and Meier, 2001) and RanBP1 (Kim et al, 2001). Plant homologs of importin α (Hubner et al, 1999;Jiang et al, 1998a;Jiang et al, 2001) and importin β (Jiang et al, 1998b) have also been shown to mediate nuclear transport in animal cell systems, although with somewhat different properties than the homologous yeast and mammalian proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Some further unique features of the classical nuclear import pathway in plants have also been noted. In Arabidopsis thaliana, Impa has been reported to mediate nuclear transport independent of Impb (Hübner et al, 1999). Impa proteins from Arabidopsis and rice (Oryza sativa) display broader specificity than their mammalian counterparts (Hicks and Raikhel, 1995;Smith et al, 1997;Jiang et al, 1998;Tzfira et al, 2000).…”
Section: Introductionmentioning
confidence: 99%